(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The gig economy has emerged as a transformative force in contemporary labor markets, reshaping the dynamics of corporate hiring and individual employment preferences. This study delves into the factors that underpin the perceived importance given to the gig economy, encompassing both cost and non-cost considerations. Through rigorous analysis, the research reveals several pivotal findings. Cost-related factors play a crucial role in shaping the significance of gig hiring. Organizations that prioritize cost benefits, such as overall savings and high acquisition costs, are more likely to attribute greater importance to gig workers. The potential for statutory levy exemptions further amplifies this trend, emphasizing the importance of regulatory considerations.